Keystone Microbiomes Revealed by 14 Years of Field Restoration of the Degraded Agricultural Soil Under Distinct Vegetation Scenarios - Zhang, Zhiming; Han, Xiaozeng; Yan, Jun; Zou, Wenxiu; Wang, Entao; Lu, Xinchun; Chen, Xu (Frontiers in Microbiology, 2020)
Agricultural intensification accelerates the degradation of cropland, and restoration has been managed by changing its vegetation. However, the keystone microbiome that drives the decomposition of plant-associated organic matter in the restoration is poorly understood. In this study we established a 14-year field restoration experiment on a degraded cropland with four treatments: (1) bare land soil without biomass input (BL); (2) maize cropland (CL) without fertilization and biomass input; (3) natural grass land (GL) and (4) alfalfa cropland (AL) with biomass left in the fields. Analyses of carbon source metabolism and high-throughput sequencing of 16S rRNA genes of the soil microbial community showed that GL and AL treatments significantly enhanced the soil physiochemical properties, including soil organic carbon (SOC), total N (TN), exchangeable N (EN) and available phosphorus (AP), compared to the BL and CL controls. Real-time quantitative PCR further revealed significant higher abundance of bacteria (16S rRNA gene copies) in GL and AL soils than in BL and CL, and similar results were obtained for microbial activities revealed by carbon utilization efficiency. In all treatments, the dominant phyla, Proteobacteria, Actinobacteria, and Acidobacteria, remained unchanged, although their relative abundance varied greatly. While the genera Reyranella, Mesorhizobium, Devosia, Haliangium, Nocardioides and Pseudonocardia were significantly more abundant in GL and AL than that in CL and BL. Bacillus were reduced 2.05, 5.15 and 3.57-fold in the CL, GL and AL, respectively, compared to that in BL. Therefore, the genera Bacillus and Cyanobacteria could be the keystone taxa as bio-indicators for monitoring the restoration of soil. Statistical analysis showed that soil SOC and pH were significantly correlated with the input of plant-associated organic matters. Conclusively, AL and GL were effective strategies for restoration of the degraded cropland by improving the physiological metabolisms of keystone microbiomes in association with decomposition of plant-associated organic matter.